Kobieta ciężarna i ciąża w polskim piśmiennictwie medycznym w pierwszej połowie XIX wieku - Kurowska, Hanna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2014)
Polish medical literature in the first half of the nineteenth century which was devoted to pregnant women was rich. It was usully largely translations of foreign works. Both practical guides for pregnant women, and professional manuals directed to midwives (accoucheuse) were published. Defined insemination, accurately determined the duration of pregnancy, reported the development of the fetus in utero, determined its size and appearance, knew causes of certain disorders in pregnancy, described the symptoms of impending childbirth. Unfortunately, in a complicated pregnancy or childbirth the medicine could not help. To woman was recommended above all peace, advised choice of a trusted midwife and tried not to interfere in a mechanical manner in pregnancy or childbirth later. A pregnant woman does not have a direct impact on the health and development of the fetus, but pointed out that to maintain the pregnancy often decided her health condition and physical abilities. Polish midwifery art drew on the achievements of medicine of English, French, and above all with the Prussian and Austrian medicine.